Single ray amputation in traumatic injury of the hand: review of literature - Filippo, Calderazzi (Acta Biomed, 2019)
Background and aim of the work: Ring avulsion are relatively common hand lesions and are associated with significant disability, especially in hand-workers. The treatment choice is still debatable. We sought to conduct a detailed systematic review in attempt to collate evidence on functional, cosmetic and patient-reported outcomes (PROs) following ray amputation for the management of traumatic hand injury and ring avulsion injury. Methods: Using the PubMed database we made a systematic search for articles regarding single ray amputation after traumatic hand lesion. Nine articles met our including criteria and were analysed. Results: Most of the included studies suggest that for those worse cases ray amputation still represent a good option. Indeed ray resection can eliminate the gap, remove a cumbersome or painful digit and guarantes better cosmesis but reduces grip and pinch strength (from 15% to 30%) and decreased palm width. Conclusions: Different surgical techniques are available, almost all of them results in a loss of strength but ensure good both functional and cosmetic results. (www.actabiomedica.it)